Analysis of Self-Medication of Cholesterol Drugs in Type 2 DM Patients at Pharmacy X Sidoarjo - Purwati, Ely; Atikah Safitri, Rifdah; Priyoherianto, Andri (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Background: Type 2 diabetes mellitus (T2DM), which frequently coexists with dyslipidemia, accounts for 85–90% of diabetes cases in Indonesia. Due to mild or ambiguous hypercholesterolemia symptoms, many patients self-medicate. Risks can arise from improper self-medication, particularly for T2DM patients taking antidiabetic medications. Objective: The purpose of this study is to characterize how T2DM patients at Pharmacy X, Sidoarjo, self-medicate cholesterol medications and examine the connection between self-medication and lipid levels. Methods: From May to July 2025, 60 purposively sampled T2DM patients who purchased cholesterol medications without a prescription participated in a cross-sectional survey. Questionnaires were used to gather information on self-medication behaviors, adherence, side effects, cholesterol levels, and demographics. Analysis was done using Spearman correlation and descriptive statistics. Result: 13.3% of patients had poor self-medication behavior, 21.7% had moderate behavior, and 65% had good behavior. Fewer people selected the right medications (68.3%), dosages (63.3%), and side effect awareness (58.3%), even though the majority knew the right indications (88.3%) and patient suitability (91.7%). Self-medication behavior had a negative correlation with triglycerides (ρ=-0.333, p=0.009) and total cholesterol (ρ=-0.533, p<0.001). Conclusion: the majority of Pharmacy X’s type 2 diabetes patients showed good self-medication practices. Self-medication behavior and total cholesterol were found to be significantly correlated negatively. suggesting that lower lipid levels are linked to improved self-medication.